Optimization of Chemi-adsorption, EDLC, and Redox Capacitance Through Electro-precipitation Synthesis of Fe3O4/NiO@rGO/h-BN for the Development of Hybrid Supercapacitor - Saha, Sanjit; Jang, Wooree; Murmu, Naresh C.; Koo, Hyeyoung; Kuila, Tapas (WILEY-V C H VERLAG GMBH, 2019)
3D Fe3O4/NiO was grafted on to the 2D rGO/h-BN by electro-precipitation method. Nitrogen of h-BN moiety and oxygen functional groups of rGO played the role of negative active site to trap the metallic cations. Electrochemical charge storage mechanism was optimized by controlling the stoichiometry and defect contents of Fe3O4/NiO@rGO/h-BN. Stoichiometry of the electro-precipitated samples was tailored in presence of negative active sites of rGO/h-BN and applied D.C. bias of the electrochemical bath. In addition, the nucleation and growth of metal oxides were influenced by the stacking and vacancy defects of rGO/h-BN sheets. High specific capacitance (1328 F g(-1)) of Fe3O4/NiO@rGO/h-BN was attributed to the synergistic effect of electrochemical double layer capacitance of rGO, chemi-adsorption of -OH ions on Lewis acid (boron of h-BN moiety) and redox capacitance of Fe3O4/NiO in alkaline medium. In addition, the presence of pyrrolic defect at the rGO/h-BN stacking region acted as the nucleation site and provided additional redox capacitance by shifting the Fermi level towards the valance band. An asymmetric supercapacitor (ASC) was constructed using Fe3O4/NiO@rGO/h-BN and thermally reduced GO as positive and negative electrode, respectively. ASC showed high energy (82 W h Kg(-1)) and power density (5600 W Kg(-1)) along with low relaxation time constant (2.2 ms) and high stability (79%) after 10,000 charge discharge cycles.